تاثيرات الاخطاء المساحية في جمالية المدن (Journal of Planner and Development, 2005)
this research presents an analytical study of the direct and indirect impacts od the survey mistakes and errors in the visual satisfaction for the towns > Iskan sector in Hilla city has been chosen as a cases study Detail survey for this area is prepared . this local survey has been compared with Iskan sector plan . The result show differences . these differences give an indication of percentage of achieving objectives for the sector plan